Domestication of wild tomato is accelerated by genome editing - Li T.; Yang X.; Yu Y.; Si X.; Zhai X.; Zhang H.; Dong W.; Dong W.; Xu C.
Crop improvement by inbreeding often results in fitness penalties and loss of genetic diversity. We introduced desirable traits into four stress-tolerant wild-tomato accessions by using multiplex CRISPR-Cas9 editing of coding sequences, cisregulatory regions or upstream open reading frames of genes associated with morphology, flower and fruit production, and ascorbic acid synthesis. Cas9-free progeny of edited plants had domesticated phenotypes yet retained parental disease resistance and salt tolerance.
Keywords: CROP; TOMATO; GENOME